1978
DOI: 10.1007/bf00312882
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary bimanual synkinesis combined with hypogonadotropic hypogonadism and anosmia in four brothers

Abstract: A new genetic syndrome of the combined occurrence of hypogonadotropic hypogonadism, anosmia (Kallmann syndrome) and congenital mirror movements in four brothers is presented. Mirror movements were manifest only within the distal parts of the upper extremities and resembled congenital mirror movements described for isolated or familial cases or those occurring in combination with other genetic defects. The hypothesis is supported, that a midline fusion disorder with preponderance of uncrossed pyramidal tract fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…These involuntary movements are thought to be due to either abnormal development of the ipsilateral corticospinal tract [Conrad et al, 1978] or lack of transcallosal inhibition [Dennis, 1976;Nass, 1985;Danek et al, 1992]. Synkinesis has been reported in KS patients with mutations in FGFR1, PROK2, and PROKR2, but is most commonly seen in patients with KAL1 mutations.…”
Section: Discussionmentioning
confidence: 97%
“…These involuntary movements are thought to be due to either abnormal development of the ipsilateral corticospinal tract [Conrad et al, 1978] or lack of transcallosal inhibition [Dennis, 1976;Nass, 1985;Danek et al, 1992]. Synkinesis has been reported in KS patients with mutations in FGFR1, PROK2, and PROKR2, but is most commonly seen in patients with KAL1 mutations.…”
Section: Discussionmentioning
confidence: 97%
“…30 The authors suggested that uncrossed pyramidal tract fibers could be a major pathogenic factor for the occurrence of congenital MM. In a previous study, a deficient inhibitory mechanism between the right and left supplemental motor cortex was suggested as the MM etiology in patients presenting corpus callosum agenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities of the corpus callosum and of pyramidal decussation in the cervical region have been considered above; other theories involving neural topography have also been considered, including inhibition of bilateral cerebral representation.20 loss of suppression of bilateral activity,75 impaired inhibitory function of the parietal lobe,2' 24 and use of ipsilaterally projecting corticospinal pathways.31 37 71 The case reported by Haerer and 595 Currier70 is of particular importance in this context. A patient with congenital and familial mirror movements sustained a cerebral infarction leading to a right hemiplegia; mirror movements persisted in the hand which'otherwise remained completely flacc'id and paralysed.…”
Section: Movementsmentioning
confidence: 99%